Tapping into the physiological responses to mistletoe infection during heat and drought stress. (6th October 2021) - Griebel, Anne; Peters, Jennifer M R; Metzen, Daniel; Maier, Chelsea; Barton, Craig V M; Speckman, Heather N; Boer, Matthias M; Nolan, Rachael H; Choat, Brendan; Pendall, Elise
Abstract: Mistletoes are important co-contributors to tree mortality globally, particularly during droughts. In Australia, mistletoe distributions are expanding in temperate woodlands, while their hosts have experienced unprecedented heat and drought stress in recent years. We investigated whether the excessive water use of mistletoes increased the probability of xylem emboli in a mature woodland during the recent record drought that was compounded by multiple heatwaves. We continuously recorded transpiration (T_SLA ) of infected and uninfected branches from two eucalypt species over two summers, monitored stem and leaf water potentials (Ψ ) and used hydraulic vulnerability curves to estimate percent loss in conductivity (PLC) for each species. Variations in weather (vapor pressure deficit, photosynthetically active radiation, soil water content), host species and % mistletoe foliage explained 78% of hourly T_SLA . While mistletoe acted as an uncontrollable sink for water in the host even during typical summer days, daily T_SLA increased up to 4-fold in infected branches on hot days, highlighting the previously overlooked importance of temperature stress in amplifying water loss in mistletoes. The increased water use of mistletoes resulted in significantly decreased host Ψ _leaf and Ψ _trunk . It further translated to an estimated increase of up to 11% PLC for infected hosts, confirming greater hydraulic dysfunction of infected trees that place them at higher risk of hydraulic failure. However, uninfected branches of Eucalyptus fibrosa F.Muell. had much tighter controls on water loss than uninfected branches of Eucalyptus moluccana Roxb., which shifted the risk of hydraulic failure towards an increased risk of carbon starvation for E. fibrosa . The contrasting mechanistic responses to heat and drought stress between both co-occurring species demonstrates the complexity of host–parasite interactions and highlights the challenge in predicting species-specific responses to biotic agents in a warmer and drier climate.